PTF11rka: an interacting supernova at the crossroads of stripped-envelope and H-poor superluminous stellar core collapses. Issue 3 (27th July 2020) - Pian, E; Mazzali, P A; Moriya, T J; Rubin, A; Gal-Yam, A; Arcavi, I; Ben-Ami, S; Blagorodnova, N; Bufano, F; Filippenko, A V; Kasliwal, M; Kulkarni, S R; et al.
ABSTRACT: The hydrogen-poor supernova (SN) PTF11rka ( z = 0.0744), reported by the Palomar Transient Factory, was observed with various telescopes starting a few days after the estimated explosion time of 2011 December 5 UT and up to 432 rest-frame days thereafter. The rising part of the light curve was monitored only in the R PTF filter band, and maximum in this band was reached ∼30 rest-frame days after the estimated explosion time. The light curve and spectra of PTF11rka are consistent with the core-collapse explosion of a ∼10 M⊙ carbon–oxygen core evolved from a progenitor of main-sequence mass 25–40 M⊙, that liberated a kinetic energy E k ≈4 × 10 51 erg, expelled ∼8 M⊙ of ejecta, and synthesized ∼0.5 M⊙ of 56 Ni. The photospheric spectra of PTF11rka are characterized by narrow absorption lines that point to suppression of the highest ejecta velocities (≳ 15 000 km s −1 ). This would be expected if the ejecta impacted a dense, clumpy circumstellar medium. This in turn caused them to lose a fraction of their energy (∼5 × 10 50 erg), less than 2 per cent of which was converted into radiation that sustained the light curve before maximum brightness. This is reminiscent of the superluminous SN 2007bi, the light-curve shape and spectra of which are very similar to those of PTF11rka, although the latter is a factor of 10 less luminous and evolves faster in time. PTF11rka is in fact more similar to gamma-ray burst SNe in luminosity, although it has a lower energy and a lower E k / M ej ratio.